The Oil Nouveau-Riche and Arms Imports - Vezina, Pierre-Louis (World Bank, Washington, DC, 2020)
Countries that strike it rich when exploring for oil and gas often fail to see growth materialize. This paper shows that one way things can get messy is via squandering new wealth, based on future resource revenues, on arms imports. In the five years following a giant oil or gas discovery, arms imports increase by 25 percent. The effect is even larger, at 51 percent, when the price of oil is as high as $80 per barrel. These estimates can be interpreted causally as the timing of giant oil discoveries is unpredictable due to the uncertain nature of exploration.